Fas Ligand Gene (Faslg) Plays an Important Role in Nerve Degeneration and Regeneration After Rat Sciatic Nerve Injury - Li, Yuting; Sun, Yuhua; Cai, Min; Zhang, Huanhuan; Gao, Nannan; Huang, Huiwei; Cui, Shusen; Yao, Dengbing (Frontiers in Molecular Neuroscience, 2018)
Wallerian degeneration (WD) is associated with changes in the expression levels of a large number of genes. However, the effects of these up- or down-regulated genes are poorly understood. We have reported some key factors that are differentially regulated during WD in our previous research. Here, we explored the roles of Fas ligand gene (Faslg) in WD after rat sciatic nerve injury. The data showed that Faslg was up-regulated in injured nerves. Expression changed of Faslg in Schwann cells (SCs) resulted in alterations in the release of related factors. Silencing or overexpression of Faslg affected SC proliferation, migration, and apoptosis through β-catenin, nuclear factor-κB, and caspase-3 pathways in vivo and in vitro. Our data suggest that Faslg is a key regulatory gene that affects nerve repair and regeneration in peripheral nerve injury. This study sheds new light on the effects of Faslg on peripheral nerve degeneration and/or regeneration.